China's Belt and Road Initiative Implementation Maneuvers in the South Pacific Region - Sihaloho, Rezya Agnesica Helena; Prabowo, Tri Bagus; Pamungkas, Cahyo (Nation State: Journal of International Studies, 2024)
The geopolitical ascendancy of China's Belt and Road Initiative (BRI) within the South Pacific Region has been extensively scrutinized due to its potential to both align with global development agendas and provoke sovereignty concerns among recipient nations. It is hypothesized that the BRI could either exacerbate debt dependencies or foster economic emancipation depending on the governance responses of the recipient countries. Therefore, this study seeks to analyze the strategic deployments and the consequential geopolitical ramifications of the BRI, particularly focusing on South Pacific nations. A qualitative method, utilizing literature reviews and analyses of secondary data sources, was systematically employed to extract and synthesize relevant insights. Empirical evidence from multiple South Pacific case studies reveals that these nations have the capacity to harness the initiative for economic enhancement without necessarily succumbing to compromised sovereignty. These findings illuminate the dual potential of the BRI to either ensnare recipient nations in dependency cycles or empower them through strategic economic engagement, contingent upon the negotiation dynamics and governance acumen of the recipient countries.